To study the factors influencing millennial’s purchasing behavior towards smart phones / Muhammad Afiq Noor Azam - Noor Azam, Muhammad Afiq (Faculty of Business and Management, 2020)
Millennial are considered as the technology savvy generation. They were born in the technology era, in other words, it is impossible to see them without smart phone in their hands. Millennial are network citizens who are very comfortable and familiar with devices and technology, and obsessed with social media (Bolton, 2013). The purpose of this study is to find out what influence them to purchase a smart phone. The variables that were included in this research was Brand Awareness. According to (Catherine Njoki Muigai, 2017), branding has become an important aspect in the eyes of the Millennial as they seek to purchase a brand that can express themselves and satisfy their needs. Price on the other hand as stated by (Hyllegard, 2011), Millennial are the generation that cares about the environment therefore this makes them willing to spend on products or services that serve in good purposes. Next, Brand Experience as stated by (Williams and Page, 2010), states that Millennial prefers and values a product or services that gives them positive experience. Lastly, for Social Reference Group as stated by (Suki and Suki, 2013) Millennial are tend to be influenced by their circles of social when it comes to their dependency towards smart phones. These were the variables that has been tested in this study to investigate which one of them influence the most on the Millennial’s purchasing behaviour towards smart phones. The survey was done by distributing set of questionnaires by using Likert scale method. The questionnaires was distributed through online survey and the researcher managed to gain 169 respondents. Reliability test, Pearson Correlation Analysis and Multiple Regression Analysis has been used to find the result. The findings indicates that Brand Experience influence most of the respondent when it comes to purchasing a smart phones.